Flower bud differentiation in banana - Meena Koshy (Department of Horticulture, College of Agriculture, 1989)
Studies were undertaken at the College of Agriculture, Vellayani during 1987 – 88 in Robusta, Palayankodan and Red Banana cultivars to determine the site, time and histological aspects of flower bud differentiation. The time of differentiation varied in the three varieties. The transition from vegetative to reproductive stage occurred in Robusta between 228 and 278 days, in Palayankodan between 250 and 311 days and in Red Banana between 334 and 365 days. The apical meristem visualized as a flat dome – like structure in the vegetative phase changed into a conical structure during the transition. After this, the conical apex became more meristematic and the bracts separated spirally from the flank meristem. In the axils of the boat shaped bracts, hand primordia developed. Later on, floral primordial were seen to develop in acropetal succession. Basic differences were not observed in respect of the histological features of differentiation among the three cultivars. With respect to morphological characters, there was rapid increase in the height and girth of the pseudostem during the vegetative and early stage of reproductive phase. The leaf area was the maximum in Red Banana plants at the transition phase. The number of functional leaves in the three developmental phases ranged from 9 to 11 in the three cultivars. The present studies could not indicate any definite role for CHO, N or C/N ratio on the induction of flowering in banana. Further studies with tissue – cultured plants have been suggested to generate accurate data on the time of occurrence of the developmental stages.